CRISP3 glycoprotein: a good biomarker for prostate cancer? - Aparecida de Lourdes Carvalho; Sebastião A. Pinto; Wagner G. dos Santos (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT Introduction: Cysteine-rich secretory protein 3 (CRISP3) is expressed at low levels in normal human prostate but often overexpressed in prostate cancer (PCa). The relevance of this overexpression for the malignancy of PCa is still unclear. The prognostic value of the currently used prostate specific antigen (PSA) test can be misleading under certain circumstances, resulting in overtreatment of indolent tumors. New biomarkers are needed to reduce overtreatment and improve quality of life of men. Objective: Evaluate if CRISP3 expression could be a good biomarker for PCa. Methods: CRISP3 expression was determined by immunohistochemistry in tissue sections of prostate cancer from twenty-five patients subjected to radical prostatectomy. Gleason grading system was used as prognostic indicator and the staging of PCa was defined using the TNM system. Clinical parameters and PSA levels before and after surgery were determined. Results: CRISP3 expression was strong in 14 (56%), moderate in four (16%) and weak in seven (28%) specimens. There was no correlation between the intensity of CRISP3 expression and pre- and post-treatment PSA levels. Fifteen (60%) of PCa biopsies showed extension of the primary tumor pT2. Seven patients (28%) showed Gleason score higher than 7; thirteen (52%) equal to 7, and five (20%) lower than 7. There were no significant statistical differences between Gleason score and CRISP3 expression. Conclusion: CRISP3 is expressed in prostate cancer at different levels. Additional studies are required to better evaluate if CRISP3 could be used as a biomarker.